2020
DOI: 10.1111/vsu.13398
|View full text |Cite
|
Sign up to set email alerts
|

Removal of lower urinary tract stones by percutaneous cystolithotomy: 68 cases (2012–2017)

Abstract: Objective To describe the use and outcome of percutaneous cystolithotomy (PCCL) for removal of urethral and bladder stones in dogs and cats. Study design Retrospective case series. Animals Sixty‐eight client‐owned dogs and cats. Methods Records were reviewed and analyzed for dogs and cats that underwent PCCL between January 2012 and December 2017. Signalment, clinical presentation, laboratory and imaging data, procedure time, use of lithotripsy, biopsy, perioperative and immediate postoperative complications, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 20 publications
1
34
1
Order By: Relevance
“…Antegrade cystoscopy through a percutaneous approach could be performed in male cats as an alternative. 34 In one cat, retrograde catheterization was not possible because of a stricture at the perineal urethrostomy site. Fluoroscopically guided percutaneous antegrade urethral catheterization could have been performed in this patient to inject contrast and gain urethral access as an alternative method to confirm the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Antegrade cystoscopy through a percutaneous approach could be performed in male cats as an alternative. 34 In one cat, retrograde catheterization was not possible because of a stricture at the perineal urethrostomy site. Fluoroscopically guided percutaneous antegrade urethral catheterization could have been performed in this patient to inject contrast and gain urethral access as an alternative method to confirm the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This inherent anatomic challenge emphasizes the necessity for postoperative imaging. Previous reports document incomplete removal of uroliths in up to 20% patients, [2][3][4][5][6][7] but since postoperative radiographs are not always performed, the true incidence is unknown. Imaging modalities such as abdominal ultrasound or contrast cystourethrography could also be considered postoperatively to ensure complete urolith removal.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term recurrence or pseudo-recurrence (calculi left behind previously) of cystic calculi was not included in this study, but has been reported in approximately 13-21% of patients. [4][5][6] The last variable considered was postoperative complications. Five of six cats with reported postoperative complications were from the open group, but this difference did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations